Atrial Fibrillation and Declining Physical Performance in Older Adults: The Health, Aging, and Body Composition Study. (May 2016) - Magnani, Jared W.; Wang, Na; Benjamin, Emelia J.; Garcia, Melissa E.; Bauer, Douglas C.; Butler, Javed; Ellinor, Patrick T.; Kritchevsky, Stephen; Marcus, Gregory M.; Newman, Anne; Phillips, Caroline L.; Sasai, Hiroyuki; et al.
Abstract : Background—: Age is the foremost risk factor for atrial fibrillation (AF), and AF has a rising prevalence in older adults. How AF may contribute to decline in physical performance in older adults has had limited investigation. We examined the associations of incident AF and 4-year interval declines in physical performance at ages 70, 74, 78, and 82 years in the Health, Aging, and Body Composition (Health ABC) Study. Methods and Results—: Health ABC is a prospective cohort of community-dwelling older adults (n=3075). The study conducted serial assessments of physical performance with the Health ABC physical performance battery (scored 0–4), grip strength, 2-minute walk distance, and 400-m walking time. Incident AF was identified from the Center for Medicare and Medicaid Services and related to 4-year interval decline in physical performance. After exclusions, the analysis included 2753 Health ABC participants (52% women, 41% black race). Participants with AF had a significantly greater 4-year physical performance battery decline than those without AF at age 70, 74, 78, and 82, with mean estimated decline ranging from −0.08 to −0.10 U (95% confidence interval, −0.18 to −0.01; P <0.05 for all estimates) after multivariable adjustment. Grip strength, walk distance, and walk time similarly showed significantly greater declines at each 4-year age interval in participants with AF. Conclusions—: In community-based cohort older adults, incident AF was associated with increased risk of decline in physical performance. Further research is essential to identify mechanisms and preventive strategies for how AF may contribute toward declining physical performance in older adults. Abstract : Supplemental Digital Content is available in the text.